<span>x=<span>−<span><span>2<span> and </span></span>y</span></span></span>=<span>−<span>2
</span></span>A.(−2, −2)
Answer:
The first statement is true.
Step-by-step explanation:
The function is f(x) = - (x + 6)(x + 2)
⇒ f(x) = - x² - 8x - 12
Now, condition for a function f(x) to be increasing at x = a is f'(a) > 0.
Now, f(x) = - x² - 8x - 12
⇒ f'(x) = -2x - 8 {Differentiating with respect to x}
Now, f'(a) = -2a - 8 {Here a can be any real value}
And, the condition for increasing function at x = a is
- 2a - 8 > 0
⇒ - 2a > 8
⇒ a < - 4
Therefore, the first statement is true i.e. the function is increasing for all real values of x where x < – 4. (Answer)
The solution of the inequality is t<-3. Because -15 divided by 5t is equal to -3
Answer:
ftudhdldkdjfjdn cbgffrwwof